Relative roles of anthropogenic aerosols and greenhouse gases in land and oceanic monsoon changes during past 156 years in CMIP5 models. Issue 10 (21st May 2016) - Zhang, Lei; Li, Tim
Abstract: Relative roles of anthropogenic aerosols (AAs) and greenhouse gases (GHGs) in land and oceanic monsoon changes during boreal summer over the period 1850–2005 in Coupled Model Intercomparison Project Phase 5 (CMIP5) models are explored. It is found that the GHG effect dominates rainfall trend over oceanic monsoon region. As a result, precipitation over western North Pacific (WNP) monsoon region and Intertropical Convergence Zone (ITCZ) over tropical eastern Pacific are strengthened through the so‐called "richest‐get‐richer" mechanism. Over land monsoon region, GHG and AA effects are different over India and East Asia (EA). The two effects tend to offset each other over India, but the AA effect dominates over EA and induces a drying trend. The weakened effect of GHGs on EA is attributed to the large offset of thermodynamic and dynamic effects associated with GHGs. While the former tends to strengthen EA rainfall through increased moisture, the latter tends to decrease EA rainfall due to the strengthened WNP monsoon impact. Key Points: GHG and AA effects tend to offset each other over India GHGs play a dominant role in oceanic monsoon changes East Asia rainfall trend is dominated by the AA effect